2010
DOI: 10.4049/jimmunol.0904038
|View full text |Cite
|
Sign up to set email alerts
|

Isoallergen Variations Contribute to the Overall Complexity of Effector Cell Degranulation: Effect Mediated through Differentiated IgE Affinity

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
5
31
1
Order By: Relevance
“…Such clonally related sequences were not iden- tified in our relatively large sequence collection (data not shown), indicating 1) that, within the overall repertoire, clonally related IgG4 and IgE transcripts may be less common than anticipated or 2) that the sample volume is too small to harbor a large collection of the available specificities. This idea is consistent with the suggestion by Davies et al (56,64,65) that atopic sensitization is predominantly caused by IgE production through the direct route, as even low-affinity IgE is sufficient to catch allergen and to trigger basophils. Moreover, several studies indicate that maximum Ag affinity neither is achieved by a maximum somatic mutation rate nor is the primary criterion for class switch recombination (66).…”
Section: Discussionsupporting
confidence: 80%
“…Such clonally related sequences were not iden- tified in our relatively large sequence collection (data not shown), indicating 1) that, within the overall repertoire, clonally related IgG4 and IgE transcripts may be less common than anticipated or 2) that the sample volume is too small to harbor a large collection of the available specificities. This idea is consistent with the suggestion by Davies et al (56,64,65) that atopic sensitization is predominantly caused by IgE production through the direct route, as even low-affinity IgE is sufficient to catch allergen and to trigger basophils. Moreover, several studies indicate that maximum Ag affinity neither is achieved by a maximum somatic mutation rate nor is the primary criterion for class switch recombination (66).…”
Section: Discussionsupporting
confidence: 80%
“…Basophil tests have found that natural variants, including the most disparate Der p 2.0101 and Der p 2.0104, induce almost identical degranulation, 17 which would be expected from our finding showing that although they were different, the antibody titers to all the variants were high. Our study on IgE binding and competition, however, indicates that targeting the 4 residues with less conservative substitutions could be a strategy for developing hypoallergic Der p 2.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, we generated a number of fully human or chimeric recombinant IgE antibodies with very well-described characteristics (Christensen et al, 2008). These antibodies were cloned by phage display, from hybridoma cell lines or made by chain-shuffling of heavy-and light antibody resulting in a total of thirty-one well-expressing recombinant IgE clones (Christensen et al, 2008(Christensen et al, , 2010. The relative binding sites on Der p 2 were determined for all thirty-one IgE antibodies, and three groups were identified which would bind Der p 2 independently of each other, i.e.…”
Section: Importance Of Ige Repertoire Diversity: Basophil Activation mentioning
confidence: 99%